Numerical and experimental analysis on the non-uniform inflow characteristics of a reactor coolant pump with a steam generator channel head. Issue 1 (1st January 2020) - Yuehui, Wang; Zhongbin, Xu; Pengfei, Wang; Jiaming, Wang; Xiaodong, Ruan
ABSTRACT: Distorted inflow caused by the complex structure of the steam generator channel head (SGCH) occurs at the entrance to the reactor coolant pump (RCP) in the AP1000 system, which may generate impeller cracks and result in deterioration of performance and stability. In this paper, to analyze the influence of distorted inflow on flow properties of the RCP, the inflow distortion characteristics are studied by a full three-dimensional steady and unsteady numerical simulation. The simulation model was verified experimentally by testing the RCP with a straight pipe and a channel head at different flow rates. Using this model, the inlet distortion was quantified and the variation law of different distortion was obtained. The results showed that a non-uniform swirling flow under lateral pressure differences was formed when the pump was coupled with a channel head instead of a straight pipe, leading to the destruction of circular symmetry of the inflow field. Further increasing the tube length alone was not effective in improving the inflow field of the RCP, and the inlet swirl effect always existed. As the distorted flow entered the pump with a pair of vortices, the chaotic flow field imposed a non-uniform stress on each blade of the impeller, resulting in the unevenly distributed flow rate of each flow-path of the blade. Then, in the flow channels of the impeller, there were obvious asymmetrical vortex core regions, even in opposite directions, which originally formed in the inflow field of the RCP and raised the risk of blade fatigue failure. Owing to the significant effects of inflow distortion produced by the SGCH, understanding the mechanism of non-uniform inflow characteristic is of great value to the design and optimization of the RCP. Abbreviations: RCP: reactor coolant pump; SG: steam generator; SGCH: steam generator channel head